HUBUNGAN DISIPLIN KELUARGA KRISTEN DENGAN TINGKAH LAKU ANAK USIA 9-12 TAHUN GEREJA BNBKP GLORIA DESA URBAN AEK MUARA PINANG SIBOLGA SELATAN 2017 . - Murnibudi Arti Halawa (IAKN Tarutung, 2018)
Abstract, This research aims to know the relationship of christian families with the behavior of children aged 9-12 years in the church BNKP Gloria urban village Aek Muara Pinang Sibolga South 2017. Research hypothesis is there is a positive relationship between the discipline of the christian family with the behavior of children ages 9-12 year in the church BNKP Gloria urban Aek Muara Pinang Sibolga South 2017. This research is a correlational research using descriptive and inferential statistical techniques. The population is all children aged 9-12 years in church BNKP Gloria amounted to 36 people. The sample is the entire population, thus this study is a population study. The research instrument is a closed questionnaire. Result of analysis value rxy = 0, 523 rtable = 0, 329 and t count = 3, 578 t table = 2,042 show Ho rejected and Ha accepted that there is a positive relationship between family discipline of christen with behaviorof child age 9-12 year. This study concluded that the discipline of christian families has a relationship with the behaviour of children aged 9-12 years. In connection with the results of this study, the authors provide input for the observers, especially “Christian Parents” to improve family discipline so that the behavior of children aged 9-12 years can be built. Keywords: Christian family discipline, Children’s behavior